2015
DOI: 10.1539/joh.14-0231-oa
|View full text |Cite
|
Sign up to set email alerts
|

Is high job control a risk factor for poor quality of life in workers with high autism spectrum tendencies? A cross‐sectional survey at a factory in Japan

Abstract: Norika HAYAKAWA, et al.: Autism spectrum tendencies and occupational environment associated with poor physical HRQOL among others. Conclusions: Our results suggest that AS tendencies have a negative effect on workers' HRQOL and social support is a primary factor in maintaining HRQOL. Moreover, a structured work environment can maintain physical HRQOL in workers with high AS tendencies since higher job control will be stressful. (J Occup Health 2015; 57: 419-426)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A consideration of the themes in the literature showed several gaps. First, although some studies mentioned mental health conditions in the ASD population (Hayakawa, 2015;Hurlbutt & Chalmers, 2004), the implications of these comorbid conditions for employment are rarely discussed or incorporated into job recommendations. In addition, although the literature acknowledged negative attitudes of coworkers and employers, stigma specifically related to mental health was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…A consideration of the themes in the literature showed several gaps. First, although some studies mentioned mental health conditions in the ASD population (Hayakawa, 2015;Hurlbutt & Chalmers, 2004), the implications of these comorbid conditions for employment are rarely discussed or incorporated into job recommendations. In addition, although the literature acknowledged negative attitudes of coworkers and employers, stigma specifically related to mental health was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…We used a validated Japanese version of the AQ (AQ-J) [ 27 ] with a cutoff point of 33 or greater to evaluate ALTs in our participants. Although the AQ has not been extensively used to investigate healthcare providers, AQ scores have been associated with poor mental health among factory workers [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, autistic traits are often subclinical (below the threshold of an ASD diagnosis) [2][3][4][5]. Recent epidemiological studies have revealed that autistic traits are widely distributed in the non-clinical general working population [4,6]. Autistic traits, as well as ASD, are closely associated with mood symptoms and suicidality, and some comorbid mental disorders, such as panic disorder or eating disorders, seem to be more common in patients with autistic traits than in those with ASD [7].…”
Section: Introductionmentioning
confidence: 99%